Borrowing in the Translation of Culturally Bound Expression - Ni Luh Putu Unix Sumartini; Ida Bagus Putra Yadnya (Universitas Muhammadiyah Semarang, 2018)
Translation is not only a linguistic transfer and transfer of meaning but also a cultural transfer. Although theoretically equivalence can be attained due to the universal nature of language and cultural convergence but the facts show that a language is used by speakers who often have very different culture from other speakers of language so that in the translation process it is difficult to find a synonymous equivalent especially culturally bound expression. This study tries to identify and describe the phenomena of translating culturally bound expression from Indonesian into English as a result of the translation ideology and strategy exercised by the translator. This is a descriptive translation study focusing on objective aspect of the product using unidirectional parallel bilingual corpora based on text-based theory and translator-based theory. The findings show that based on the study of Indonesian fiction with Balinese culture setting translated into English there is an effort to translate the cultural meaning with the strategy of borrowing.